Analysis of Factors Influencing the Level of Tourist Visits in the Klawalu Mangrove Tourism Area, Sorong City - Murni, Murni; Ibal, La; Alting, Saoda (Efficient: Indonesian Journal of Development Economics, 2025)
The number of tourist visits to the Klawalu Mangrove Tourism Area is still low, even though this area has enormous potential for sustainable ecotourism development that can improve the welfare of local communities and preserve the environment. The research was conducted in Klawalu Village, Sorong City, Southwest Papua. The method used was a quantitative approach through multiple linear regression analysis, with data collected through questionnaires and interviews with 40 tourists who had visited the location. The results showed that ticket price and service quality were the main factors influencing tourists' decisions to revisit. Tourists considered the suitability of price to the facilities and experience provided as determining factors. Conversely, accessibility, infrastructure, and the attractiveness of the tourist attraction did not have a significant influence.